Characterisation of multi-walled carbon nanotube reinforced epoxy resin composites - Singh S.; Srivastava V.K.; Prakash R. (My University, 2025)
The main theme of this paper is to describe the mechanical properties of multi-walled carbon nanotube (MWCNT)/epoxy resin composites with the variation of MWCNT fillers. The work tried to achieve a uniform distribution of MWCNT filler in the epoxy matrix by modifying the hardener and mixing conditions. The MWCNT fillers were used to fabricate the MWCNT/epoxy resin composites with the variation of weight percentage of 0?5, 1, 2 and 3%. The dispersion of MWCNT in epoxy resin was carried out with the help of three ball rolling mill process. A significant improvement in tensile strength, compressive strength and elastic modulus was observed due to the excellent dispersion of the MWCNT filler in the epoxy resin that give higher values of tensile strength, compressive strength and elastic modulus at 3% MWCNT. © 2013 Institute of Materials, Minerals and Mining.